Sistema IOT para el monitoreo del estado eruptivo del volcán Cotopaxi. - Barragán Yugsi, Luis David (2023)
This degree project focuses on an Internet Things development (IoT) prototype for monitoring eruptive state ofCotopaxi volcano. The main objective is to find a technological solution using LoraWan network that allows constant monitoring and early detection ofvolcanic activitysigns, providing vital information for decision making and safety of nearby communities.The first instance, an exhaustive study of necessary requirementsfor monitoring eruptive state of Cotopaxi volcano is carried out. This includes key parameters identification to be monitored, such as seismic activity, volcanic gas emission, followed by network LoraWan IoT sensors strategically distributed at different points. These sensors are equipped bystate-of-the-art technology to capture and transmit real-time data to a central monitoring platform to collect information aboutvolcanic activity.